Alpha Carbonic Anhydrase 5 Mediates Stimulation of ATP Synthesis by Bicarbonate in Isolated Arabidopsis Thylakoids - Fedorchuk, Tatiana P.; Kireeva, Inga A.; Opanasenko, Vera K.; Terentyev, Vasily V.; Rudenko, Natalia N.; Borisova-Mubarakshina, Maria M.; Ivanov, Boris N. (Frontiers in Plant Science, 2021)
We studied bicarbonate-induced stimulation of photophosphorylation in thylakoids isolated from leaves of Arabidopsis thaliana plants. This stimulation was not observed in thylakoids of wild type in the presence of mafenide, a soluble carbonic anhydrase inhibitor, and was absent in thylakoids of two mutant lines lacking the gene encoding alpha carbonic anhydrase 5 (αCA5). Using mass spectrometry, we revealed the presence of αCA5 in stromal thylakoid membranes of wild type plants. A possible mechanism of the photophosphorylation stimulation by bicarbonate that involves αCA5 is proposed.